Иван-Царевич и Змей-Горыныч - Афанасьев Александр Николаевич (Читаем в школе, 2013)
Экземпляры: ф.11 (ретро) / Инвентарный номер: 49887 / Цена: / Сис.шифр: Д / Авт.знак: А 94 / ГРНТИ: 17.82.93 / ББК: Д